Pengaruh Iklan dan Kualitas Produk terhadap Keputusan Pembelian Produk Tolak Angin Sidomuncul di Rusunawa Tambora : The Influence of Advertising and Product Quality on Purchasing Decisions for Tolak Angin Sidomuncul Products at Rusunawa Tambora - Meisa Agustin; Darkiman Ruminta; Dudi Duta Akbar (CV Warnak Johanna Nusantara, 2025)
This research has a background problem that is the tendency of rusunawa residents to generalize the benefits of Tolak Angin as a medicine that can cure various diseases. The purpose of this study is to analyze the influence of advertising and product quality on consumer purchasing decisions on Tolak Angin products in Tambora rusunawa. The data used are primary data obtained from the results of the questionnaire. This type of research uses quantitative. The population in this study is the community in Tambora rusunawa. Data collection uses Purposive Sampling samples distributed to 96 respondents. Data analysis techniques used are descriptive analysis, data quality testing, classical assumption testing, hypothesis testing and determination coefficient testing. Based on the results of this study, it shows that advertising partially has a positive and significant effect on purchasing decisions with a calculated t value of 3.060 > 1.985 and a significant value of 0.003 < 0.05. Meanwhile, partially product quality has a significant effect on purchasing decisions with a calculated t value of 6.628 > 1.985 and a significant value of 0.000 < 0.05. Likewise, simultaneously, the two independent variables, namely advertising and product quality, simultaneously have a positive and significant effect on the consumer purchasing decision variable with a calculated f value of 75,052 > 3.09 and a significant value of 0.000 < 0.05.